PHYLOGENETIC ANALYSIS OF THE FOOT AND MOUTH DISEASE VIRUS OF THE VIETNAMESE AND GLOBAL ISOLATES BASED ON THE 5'UTR AND ID(VPl) GENETIC MARKERS - Hoà, Lê Thanh; Phượng, Thái Thị Thuỷ; Xuyến, Lê Thị Kim (Vietnam Journal of Biotechnology, 2011)
Phylogenetic relationship between 6 strains ofthe Foot and Mouth Disease (FMD) collected from pigs and cattle in Tien Giang and Dong Thap (including 2 isolates from the hybrid Fl cattle) and global strains of type O, type A and type Asias-1, was established based on comparative analysis of ID(VPl) (or 1D-2A-2B) and the 5'UTR genetic markers. The FM-DTCB-H(VN) strain from pigs was grouped with those of Taiwan and Hong Kong, while strains firom the Fl hybrid cattle (FM-DTFl-Bl(VN) and FM-DTF1-B2(VN) formed a clade with the strain OIO ofthe Phillipines. Using a portion of VP1(1D-2A-1B) as a genetic marker, the phylogenetic and original relationship of 18 strains including 4 fi-om Vietnam was analyzed. As a result, all the Vietnamese strains belong to type O and clustered in group I and II, among which the strains collected from domestic pigs and cattle are oi Cathay (group I); the strain of Fl hybrid cattle is oi ME-SA (PanAsia) sublineage (group II) while strains of type A and Asia-1 formed as an out-group (group III). Apparently, the strains of FMDV from pigs and cattle in Tien Giang and Dong Thap are divided into two taxonomic groups: type O, clade Cathay; and type O, clade ME-SA(PanAsia), as the results obtained by the previous investigators.